Noninvasive Assessment and Correlation of Cardiovascular Changes among COPD Patients with Its Prognosis - Yadav, Prashant; Bhattacharya, Somnath; Kumar, Adesh; Gupta, Ashish Kumar; Gautam, Aditya Kumar; Kushwaha, Bal Krishna (Disease and Health Research: New Insights Vol. 5, 2024)
Background: Chronic obstructive pulmonary disease (COPD) often co-exists with other co-morbidities or diseases that have an enormous impact on its prognosis. A complex systemic disease with both pulmonary and extrapulmonary manifestations that are causally related or have shared risk factors. Cardiovascular changes on ECG and Echocardiography are one of the common comorbidities of COPD accounting for a 25% rise in major adverse cardiac events (like AMI, and stroke) and mortality. Hence acute cardiac abnormalities across all severity of COPD patients clearly contribute to the overall mortality and morbidity, so an understanding of their role noninvasively through this study holds potential for early intervention. Objectives: This study aimed at noninvasive assessment and correlation of cardiovascular manifestation in COPD patients with its outcome. Materials and Methods: A cross-sectional study was done in the Department of Respiratory Medicine of a rural tertiary care center on patients during the period from January 2015 to June 2016 visiting our OPD or IPD. A total of 350 study subjects were screened and those fulfilling the inclusion and exclusion criteria that were 200 consenting to participate were included in the study. COPD was diagnosed based on clinical history, clinical examination, X-ray chest, and spirometry. All patients were further subjected to electrocardiogram (ECG) and two- dimensional echocardiography (2D-ECHO) for cardiac evaluation. Data collection was done and analyzed. Results: On ECG evaluation: arrhythmia was found in 99 (49.5%) cases, right ventricular hypertrophy (RVH) in 61(30.5%) cases, and right atrial enlargement (RAE) in 52(26%) cases. Right bundle branch blocking in 20(10%) cases poor progression of R wave in 24(12%) cases and right axis deviation was found in 30 (15%) cases. On 2DECHO evaluation: Tricuspid regurgitation was found in 117(58.5%) cases, pulmonary hypertension in 116 (58%) cases, RAE in 79(39.5%) cases, RVH in74 (37%) cases, RV enlargement in 55(27.5%) cases, and left ventricular diastolic dysfunction in 113(56.05%) cases. Conclusion: Cardiovascular comorbidities are highly prevalent in moderate to very severe COPD patients who need early diagnosis and treatment. Hence ECG and ECHO are simple non-invasive bedside tools for cardiac evaluation of COPD patients during acute exacerbation as well as during the follow-up of the disease.